Concerns regarding the validity of nutrition self-efficacy questionnaire among Iranian elderly population - Saeed Pahlevan Sharif; Navaz Naghavi; Hamid Sharif Nia (BMC, 2022)
Abstract There are some statistical concerns regarding a recently published article which has claimed to develop and psychometrically evaluate an instrument to assess the nutrition self-efficacy among Iranian elderly population.